2010
DOI: 10.1053/j.ajkd.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure and Mortality Among Older Community-Dwelling Adults With CKD

Abstract: Background-Chronic kidney disease (CKD) is an increasingly common condition, especially among older adults. CKD manifests differently in older versus younger patients, with a risk of death that far outweighs the risk of CKD progressing to the point that dialysis is required. Current CKD guidelines recommend a blood pressure target of <130/80 mmHg for all CKD patients, but it is unknown how lower versus higher baseline blood pressures may affect older adults with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
2
29
0
2
Order By: Relevance
“…2 Owing to interaction between the kidney measures and hypertension, the higher relative risk of all-cause mortality conferred by hypertension disappeared at lower eGFR and higher albuminuria. Indeed, as we discussed, 2 this phenomenon has been reported in several studies 3,4 and warrants further investigation.…”
supporting
confidence: 75%
“…2 Owing to interaction between the kidney measures and hypertension, the higher relative risk of all-cause mortality conferred by hypertension disappeared at lower eGFR and higher albuminuria. Indeed, as we discussed, 2 this phenomenon has been reported in several studies 3,4 and warrants further investigation.…”
supporting
confidence: 75%
“…This association appeared to be consistent across various categories of eGFR and in those with and without albuminuria(15). A secondary analysis of the Study of Heart and Renal Protection trial noted that the U-shaped associations of blood pressure with mortality was noted only among CKD patients with underlying cardiovascular disease but not in those with pre-existing cardiovascular disease(16).…”
Section: Discussionmentioning
confidence: 77%
“…Previous observational studies in the dialysis population and in patients with less severe kidney disease have found that both higher and lower SBP and DBP were associated with a higher risk of death and CVD (9,(14)(15)(16)(17)(18)(19). A recent study by Kovesdy et al examined .600,000 veterans with CKD and found that patients in whom both SBP and DBP were very high or very low had the highest mortality rates (3).…”
Section: Discussionmentioning
confidence: 99%